Pan-cancer analysis identifies YTHDF2 as an immunotherapeutic and prognostic biomarker - Liu, Weiwei; Liu, Chaoqun; You, Jia; Chen, Zilin; Qian, Cheng; Lin, Wandie; Yu, Lina; Ye, Lele; Zhao, Liang; Zhou, Rui (Frontiers in Cell and Developmental Biology, 2022)
Background: N6-methyladenosine (m6A) modification is a dynamic and reversible post-transcriptional RNA modification prevalent in eukaryotic cells. YT521-B homology domain family 2 (YTHDF2) has been identified as a member of m6A reader protein involving in many vital biological processes, whereas its role and functional mechanisms in cancers remain unclear. Methods: Bioinformatics analyses were performed on multiple databases including GTEx, TCGA, GEO and Cbioportal to explore the connection between YTHDF2 expression and its genomic changes including tumor mutation burden, microsatellite instability and mismatch repair in 33 different cancer types. We also investigated the association of YTHDF2 expression with prognosis, immune infiltration, tumor microenvironment, immune checkpoints and chemokines. Besides, the correlation of YTHDF2 expression with copy number variation and promoter methylation was also studied in tumors compared with normal tissues. At last, we analyzed the protein-protein interacting network and related genes of YTHDF2 to enrich its potential functional mechanism in tumor development and progression. Real-time qPCR was used to verify the expression of YTHDF2-related genes in colorectal cancer cells, and immunohistochemical staining was adopted to verify immune infiltration in tissue sections from 51 hepatocellular carcinoma patients. Results: YTHDF2 was overexpressed in a majority of tumor types and associated with their poor overall survival, progression-free interval, and disease-specific survival. The correlation of YTHDF2 expression with tumor mutation burden, microsatellite instability and mismatch repair was also detected in most of the tumor types. Moreover, YTHDF2 might participate in the immune regulation through influencing the expression of immune checkpoint genes and the infiltration of immunocytes in tumor microenvironment. Notably, we demonstrated a positive correlation between YTHDF2 expression and the infiltration of CD8+ T cells and macrophages in many tumors, the result of which was verified in 51 clinic hepatocellular carcinoma tissues. In addition, the involvement of YTHDF2 in “Spliceosome” and “RNA degradation” were two potential functional mechanisms underlying its influence on tumor progression. The regulation of YTHDF2 on predicted genes has been verified in CRC cells. Conclusion: YTHDF2 might be a new therapeutic target and a potential biomarker of cancer immune evasion and poor prognosis.